2017
DOI: 10.1074/jbc.m116.769877
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-cell protection from inflammatory stress by the endoplasmic reticulum proteins thrombospondin 1 and mesencephalic astrocyte-derived neutrotrophic factor (MANF)

Abstract: Cytokine-induced endoplasmic reticulum (ER) stress is one of the molecular mechanisms underlying pancreatic β-cell demise in type 1 diabetes. Thrombospondin 1 (THBS1) was recently shown to promote β-cell survival during lipotoxic stress. Here we show that ER-localized THBS1 is cytoprotective to rat, mouse, and human β-cells exposed to cytokines or thapsigargin-induced ER stress. THBS1 confers cytoprotection by maintaining expression of mesencephalic astrocyte-derived neutrotrophic factor (MANF) in β-cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…In this study, we demonstrated that the MANF protein intensifies islet b-cell proliferation from aged mice, suggesting that MANF could partly reverse age-dependent repression of b-cell replication. Previously, we found that recombinant MANF protein partially rescues mouse and human b-cells from cytokine-and ER stress-induced cell death in culture (30,38) and induces human b-cell proliferation (30). Here, we show that Manf mRNA is upregulated in mouse b-cells in hyperglycemic conditions in vitro and that MANF protein reduces ER stress-induced glucotoxicity in mouse b-cells.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In this study, we demonstrated that the MANF protein intensifies islet b-cell proliferation from aged mice, suggesting that MANF could partly reverse age-dependent repression of b-cell replication. Previously, we found that recombinant MANF protein partially rescues mouse and human b-cells from cytokine-and ER stress-induced cell death in culture (30,38) and induces human b-cell proliferation (30). Here, we show that Manf mRNA is upregulated in mouse b-cells in hyperglycemic conditions in vitro and that MANF protein reduces ER stress-induced glucotoxicity in mouse b-cells.…”
Section: Discussionmentioning
confidence: 51%
“…We show that MANF resides in the ER where it modulates ER stress and is crucial for b-cell survival. Upon ER stress, MANF is secreted from b-cells (30), and rhMANF has protective and restorative effects when applied exogenously to human and mouse b-cells (30,38). Thus, MANF seems to have a dual mode of action: 1) cotranslationally where it inserts in the ER, thereby modulating ER stress, and 2) extracellularly (possibly through autocrine/paracrine signaling) by activating a signal transduction pathway and/or being endocytosed and transported to the ER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…153 It is interesting that this cell-protective effect was only induced by intracellular TSP1 engineered with an ER retention KDEL sequence and was not observed with conditioned medium TSP1. 153,154 In this pancreatic βcell system, ER TSP1 colocalized with protein disulfide isomerase. Further studies showed that TSP1 was also cytoprotective to β cells acutely exposed to the inflammatory cytokines interleukin-1β or interferon-γ or to thapsigargin-induced ER stress, although prolonged exposure (4-24 hr) resulted in downregulation of TSP1 expression and proteosomal degradation, leading to cell death.…”
Section: Intracellular Tsp1 As An Er Stress Regulator Of Ecmmentioning
confidence: 96%
“…Knockout of THBS1 results in mitochondrial dysfunction in mice (21). THBS1 can prevent mitochondrial pathway of apoptosis from being triggered (35) and inhibits palmitate-induced release of mitochondrial cytochrome c, cleavage of capase-3, and apoptosis (36), indicat-…”
Section: Discussionmentioning
confidence: 99%